2012
DOI: 10.1007/s10152-012-0316-1
|View full text |Cite
|
Sign up to set email alerts
|

Meiofauna as food source for small-sized demersal fish in the southern North Sea

Abstract: Meiofauna play an essential role in the diet of small and juvenile fish. However, it is less well documented which meiofaunal prey groups in the sediment are eaten by fish. Trophic relationships between five demersal fish species (solenette, goby, scaldfish, dab \20 cm and plaice \20 cm) and meiofaunal prey were investigated by means of comparing sediment samples and fish stomach contents collected seasonally between January 2009 and January 2010 in the German Bight. In all seasons, meiofauna in the sediment w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 50 publications
2
19
0
1
Order By: Relevance
“…Small gudgeons (2.5-5.0 cm L j and 6-8 cm L j) consumed sig nificantly more nematodes with a body length < 0.5 mm and 0.5-1.0 mm than did larger members of this species (10-12 cm Lt ); this may be a function of the abovementioned differences in the mean inter-raker distance and branchial openings. Ontogenetic shifts in diet from meiobenthos to larger prey items by young fish are not un common (Ellis & Coull, 1989;Coull et al, 1995;Aarnio, 2000;Schiickel et al, 2012a). Table 6.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Small gudgeons (2.5-5.0 cm L j and 6-8 cm L j) consumed sig nificantly more nematodes with a body length < 0.5 mm and 0.5-1.0 mm than did larger members of this species (10-12 cm Lt ); this may be a function of the abovementioned differences in the mean inter-raker distance and branchial openings. Ontogenetic shifts in diet from meiobenthos to larger prey items by young fish are not un common (Ellis & Coull, 1989;Coull et al, 1995;Aarnio, 2000;Schiickel et al, 2012a). Table 6.…”
Section: Discussionmentioning
confidence: 98%
“…However, copepods have an exoskeleton that is slowly digested and remains in the gut for several hours after ingestion, while nematodes are soft-bodied and are digested rapidly within 2-3 h with no visible remains (Alheit & Scheibel, 1982;Scholz et al, 1991), thus probably giving a false impression of diet composition of fish (Schiickel et al, 2012a). Nevertheless, studies in marine habitats showed that nematodes are ingested by fish (Fitzhugh & Fleeger, 1985;MacCall & Fleeger, 1993;Feller & Coull, 1995), with reductions in their abundances by up to 50%, but these results have been interpreted as a negligible side effect of sediment feeding and disturbances Cross & Curran, 2004).…”
mentioning
confidence: 99%
“…이 중 중형저서동물은 1 mm 체를 통과하고 38 µm 체 위에 남는 저서 무척추 동물을 칭한다 (Higgins and Thiel 1988). 중형저서동물 에서 주로 나타나는 분류군은 선충류(Nematoda), 저서성 요각류(Harpacticoida), 유공충류(Foraminifera), 다모류 으로 높은 서식밀도를 보이며 (Mcintyre 1969), 대형저서 동물에 비하여 생활사가 짧고 수온과 chlorophyll a 그리 고 입자성 유기탄소(POC) 등의 물리화학적 변화에 짧은 기간 내에 군집변화를 보이는 생태학적 특성을 가지며 (Sandulli and De Nicola 1990), 1차 소비자로서 어류와 다른 저서동물의 먹이원으로 역할을 하여 이들의 군집조 성에 영향을 미친다 (김 등 1998;Schückel et al 2013). 또 한, 대형저서동물에 비하여 많은 연구가 진행되어 있지 않 은 중형저서동물이지만, 몇몇 분류군들의 특징을 이용하 여 환경지수와 지표를 산출하는 연구가 진행된바 있으며 (Raffaelli and Mason 1981;김 등 1998;Geetanjali et al 2002;Bergin et al 2006;Min 2007;Moreno et al 2011;Semprucci et al 2013b), 대형저서동물군집과의 상관관계 를 통하여 저서생태계 오염에 대한 모니터링 연구에도 이 용 되고 있다 (Hummon et al 1976;Susan 1980;Flach et al 2002;Semprucci et al 2013a).…”
Section: 서 론unclassified
“…In others, fish predation on meiofauna was assumed to be nearly negligible because these prey populations are large and, with their short generation times, are able to recover very quickly such that they are not strongly impacted by the comparatively small numbers of predatory fish (Coull, ; Shaw & Jenkins, ; Cross & Curran, ). Yet, in other studies, benthic meiofauna were shown to be an important food source, especially for small and juvenile fish species (Schückel et al ., ; Weber & Traunspurger, ,b). Although this discrepancy has been attributed to differences in methodologies (e.g.…”
Section: Introductionmentioning
confidence: 99%